2008
DOI: 10.1126/science.1161121
|View full text |Cite
|
Sign up to set email alerts
|

Apobec3 Encodes Rfv3 , a Gene Influencing Neutralizing Antibody Control of Retrovirus Infection

Abstract: Recovery from Friend Virus 3 (Rfv3) is a single autosomal gene encoding a resistance trait that influences retroviral neutralizing antibody responses and viremia. Despite extensive research for 30 years, the molecular identity of Rfv3 has remained elusive. Here we demonstrate that Rfv3 is encoded by Apobec3. Apobec3 maps to the same chromosome region as Rfv3 and has broad inhibitory activity against retroviruses including HIV. Not only did genetic inactivation of Apobec3 convert Rfv3-resistant mice to a suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
235
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(249 citation statements)
references
References 25 publications
13
235
1
Order By: Relevance
“…Several studies have suggested that APOBEC BALB is less effective that APOBEC BL6 at restricting infection by F-MLV (27,30,50). However, clearly both alleles are important anti-M-MLV restriction factors, because reversion occurred with similar kinetics and frequency in the two mouse strains, and both alleles effectively inhibited reverse transcription in EnRT assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have suggested that APOBEC BALB is less effective that APOBEC BL6 at restricting infection by F-MLV (27,30,50). However, clearly both alleles are important anti-M-MLV restriction factors, because reversion occurred with similar kinetics and frequency in the two mouse strains, and both alleles effectively inhibited reverse transcription in EnRT assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that APOBEC3 BL6 more potently restricts F-MLV than the APOBEC3 BALB allele and that glyco-Gag mutant F-MLV replicates more poorly in WT mice bearing either allele than in APOBEC3 KO mice (8,27,30). To determine whether this was also the case for M-MLV, we infected C57BL/6, BALB/c, and APOBEC3 KO pups with WT and glyco-Gag mutant M-MLV; the APOBEC3 null allele is present on the BL/6 background (26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The debate over the mechanism of resistance to murine A3 (muA3) of the rodent gammaretrovirus Moloney murine leukemia virus (Mo-MLV) has not come up with a generally convincing model, despite many studies (5, 9, 13, 32, 35, 49). However, recent data clearly show that muA3 is an important in vivo restriction factor of Mo-MLV and the Friend virus complex (45,73,89).…”
mentioning
confidence: 99%